Express the Boolean function F = x + yz as product of max-terms.

This answer is restricted. Please login to view the answer of this question.

Login Now

Solution:

First, we need to convert the function into the product-of-OR terms by using the distributive law as follows

F = x + yz

F = (x + y)(x + z)

F = (x + y + zz’)(x + yy’ + z)

F = (x + y + z)(x + y + z’)(x + y + z)(x + y’ + z)

F = M0 . M1 . M2

F = Π(0, 1, 2)

If you found any type of error on the answer then please mention on the comment or report an answer or submit your new answer.
Leave your Answer:

Click here to submit your answer.

Discussion
0 Comments
  Loading . . .